Solve the equation; 3x - 2y = 7, x + 2y = -3
...Solve the equation; 3x - 2y = 7, x + 2y = -3
x = 1, y = -2
x = 1, y = 3
x = -2, y = -1
x = 4, y = -3
Correct answer is A
3x - 2y = 7; Solve by elimination method
x + 2y = -3
3x - 2y = 7.....(i)
-3x + 6y = -9.....(ii)
-8y = 16
y = 16−8=−2
Put y = -2 into equation (i); 3x - 2y = 7
3x - 2(-2) = 7
3x + 4 = 7
3x = 7 - 4
3x = 3
x = 33 = 1
Solve the logarithmic equation: log2(6−x)=3−log2x...
In the figure, determine the angle marked y ...
If M and N are two fixed points in a plane. Find the locus L = [P : PM = PN] ...
A binary operation x is defined by a x b = ab. If a x 2 = 2 - a, find the possible values of a?...
Find the remainder when 3x3 + 5x2 - 11x + 4 is divided by x + 3 ...
If X = {x : x < 7} and Y = {y:y is a factor of 24} are subsets of μ = {1, 2, 3.....
The graph of f(x) = x2 - 5x + 6 crosses the x-axis at the points...